Time-restricted feeding ameliorates dextran sulfate sodium-induced colitis via reducing intestinal inflammation - Song, Shuo; Chen, Lingling; Bai, Meijuan; Wang, Shuo; Ye, Xiaoyi; Lin, Yijun; Luo, Xuemei; Li, Zixuan; Zhang, Lingling; Zhu, Xinyu; Wang, Zinan; Chen, Yan (Frontiers in Nutrition, 2022)
Time-restricted feeding (TRF) is an emerging dietary intervention that improves metabolic disorders such as obesity, insulin resistance and dyslipidemia. Inflammatory bowel disease (IBD) is a chronic inflammatory disorder affecting the gastrointestinal tract, where nutrition plays an important role in its pathogenesis. Although numerous strategies of nutritional intervention have been reported, whether TRF can improve IBD has been elusive. In this study, we investigated the effect of two cycles of 7-day TRF intervention in a dextran sulfate sodium-induced IBD mouse model. We found that TRF was able to reduce the disease activity index and ameliorate the IBD-associated symptoms, as well as increase the number of colonic crypts and decrease the histological score in the colon. Furthermore, TRF lowered the percentage of CD4+ T cells in the peripheral blood and mesenteric lymph node, and increased the number of CD4+CD25+ T cells in the mesenteric lymph nodes. Additionally, TRF reduced the infiltration of leukocytes and macrophages around the crypt base in the colon. However, unlike the intermittent caloric restriction with fasting-mimicking diet, TRF was not able to increase the markers of progenitor and cell proliferation in the colon. Collectively, these results demonstrated that TRF is able to improve IBD in mice via reduction in intestinal inflammation.